The importance of emotional intelligence in reducing work fatigue in playgroup and kindergarten teachers - Setyawan, Nur Fachmi Budi; Luthfia, Faizatun Nisa (Research and Social Study Institute, 2024)
This study aimed to examine the relationship between the level of emotional intelligence and the level of work fatigue in playgroup and kindergarten teachers. The research participants were 100 teachers from various educational institutions at the playgroup and kindergarten levels in the Special Region of Yogyakarta. The instruments used included the emotional intelligence scale and work fatigue scale. The data collection method was through a scale distributed to participants which was then analyzed by using the Karl-Pearson product moment analysis method. The results of the data analysis showed that there was a significant negative correlation between the level of emotional intelligence and the level of work fatigue in playgroup and kindergarten teachers (r = -0.672, p < 0.001). This showed that the higher the level of emotional intelligence, the lower the level of work fatigue felt by teachers. Vice versa, the lower the level of emotional intelligence, the higher the level of work fatigue felt by the teacher. The emotional intelligence variable contributed 45.1% to work fatigue, while the remaining 54.9% was influenced by other factors. This study provided important implications for future researchers as well as administrators of educational institutions and teachers to improve the understanding and development of emotional intelligence as a strategy to reduce the level of work fatigue in teachers at the playgroup and kindergarten levels. In an effort to improve welfare and the quality of teaching, fostering emotional intelligence needed to be integrated into training and professional development programs for teachers.